1992
DOI: 10.1002/hup.470070503
|View full text |Cite
|
Sign up to set email alerts
|

Effects of benzodiazepine‐induced sedation on temporal processing

Abstract: Unlike processing of time intervals in the range of seconds or more, processing of brief durations ranging from approximately 50 to 100 ms appears to be beyond cognitive control and based on neural counting mechanisms. In a placebo-controlled study either 15 mg of midazolam or placebo were applied to 36 healthy male volunteers to investigate the effect of pharmacologically induced sedation on temporal processing of intervals in the range of milliseconds indicating performance on time perception and in the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 33 publications
2
15
0
1
Order By: Relevance
“…Our results may be seen as having parallels with Rammsayer's (1992Rammsayer's ( , 1993Rammsayer's ( , 1997Rammsayer's ( , 1999Rammsayer's ( , 2006 findings that the timing of longer intervals is more susceptible to drug effects than the timing of shorter intervals. The relative insensitivity of short interval timing to the disruptive effects of drugs has been taken as evidence against a unitary account of timing based on a single timer.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results may be seen as having parallels with Rammsayer's (1992Rammsayer's ( , 1993Rammsayer's ( , 1997Rammsayer's ( , 1999Rammsayer's ( , 2006 findings that the timing of longer intervals is more susceptible to drug effects than the timing of shorter intervals. The relative insensitivity of short interval timing to the disruptive effects of drugs has been taken as evidence against a unitary account of timing based on a single timer.…”
Section: Discussionsupporting
confidence: 86%
“…Many drug effects on timing are specific to certain time intervals: for example, the minor tranquillizer midazolam, the atypical neuroleptic remoxipride, and the NMDA receptor antagonist memantine, all reduce estimation accuracy for longer time intervals (in the range of seconds) but not for shorter intervals (in the range of hundreds of milliseconds; Rammsayer 1992Rammsayer , 1993Rammsayer , 1997Rammsayer , 1999Rammsayer , 2006, and the noradrenaline reuptake inhibitor reboxetine improves accuracy only at longer intervals (Rammsayer et al 2001). These dissociations, together with recent neuroimaging evidence (for a review see Lewis and Miall 2003) suggest that intervals below and above approximately one second are represented by two distinct timing processes that may be differentially sensitive to drug effects.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological studies complement this finding by showing that GABA agonists reduce perceptual awareness (van Loon et al, 2012) and visual discrimination (Giersch & Herzog, 2004), and attenuate the neurophysiological response to visual oddball stimuli (P3 event-related brain potential component; Watson et al, 2009). Further studies showed that GABA agonists also impair temporal discrimination of auditory intervals (Rammsayer, 1992(Rammsayer, , 1999. In addition to cortical regions, the dendritic spines of GABAergic projection neurons in the basal ganglia make contact with the corticostriatal-thalamostriatal glutamatergic and nigrostriatal dopaminergic neurons involved in interval timing (Meck, 1996).…”
Section: Individual Differencesmentioning
confidence: 95%
“…There is some debate in the literature regarding the extent to which timing of different duration values exploits different timing mechanisms (see Gibbon, Malapani, Dale, & Gallistel, 1997). For example, Rammsayer (1992Rammsayer ( , 1994Rammsayer ( , 1999Rammsayer & Lima, 1991) has claimed that timing of durations shorter than approximately 500 ms is mediated by different mechanisms than timing of intervals in the range of 1 to 2 s, although other authors have made parallel claims regarding different duration ranges (see Clarke, Ivry, Grinband, Roberts, & Shimizu, 1996;Poppel, 1996). Gibbon et al have argued that demonstrating that impairments in timing are not dissociable across different duration values would provide crucial evidence for common timing mechanisms across the range of durations.…”
Section: Methodsmentioning
confidence: 99%